Perlindungan Hukum Terhadap Korban Tindak Pidana Penipuan Transaksi Jual Beli Pada Marketplace - Yunita Amalia, Erlyna; Isnawati, Muridah (Perspektif Hukum, 2024)
The times open up opportunities for convenience in various sectors of life, especially in the context of electronic media-based buying and selling transactions on the marketplace. With these developments there are advantages and disadvantages for users. This research aims to provide an understanding of legal protection for victims of electronic transaction fraud. The focus of this problem includes two main questions, namely, legal protection for victims and legal remedies that can be taken. This research is normative in nature using a statutory approach. This normative legal research is conducted through analysis of library materials and secondary data to overcome the legal problems faced. The findings of the research show that victims get legal protection regulated by the provisions in Article 19 paragraph (1) of Law Number 8 Year 1999 concerning Consumer Protection. There are two efforts to protect and maintain consumer rights such as, out-of-court settlement as an alternative method and settlement through court channels as the last step that can be taken.